2006
DOI: 10.1016/j.physd.2006.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization processes in complex networks

Abstract: We present an extended analysis, based on the dynamics towards synchronization of a system of coupled oscillators, of the hierarchy of communities in complex networks. In the synchronization process, different structures corresponding to well defined communities of nodes appear in a hierarchical way. The analysis also provides a useful connection between synchronization dynamics, complex networks topology and spectral graph analysis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 42 publications
0
92
0
1
Order By: Relevance
“…Researchers have found that an appropriate description of such systems involves an understanding of both the dynamics of the individual oscillators and the connection topology of the network. Investigators studying the latter have found that many complex networks have a modular structure involving motifs [1], communities [2,3], layers [4], or clusters [5]. For example, recent work has shown that as many kinds of networks (including isotropic homogeneous networks and a class of scale-free networks) transition to full synchronization, they pass through epochs in which well-defined synchronized communities appear and interact with one another [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that an appropriate description of such systems involves an understanding of both the dynamics of the individual oscillators and the connection topology of the network. Investigators studying the latter have found that many complex networks have a modular structure involving motifs [1], communities [2,3], layers [4], or clusters [5]. For example, recent work has shown that as many kinds of networks (including isotropic homogeneous networks and a class of scale-free networks) transition to full synchronization, they pass through epochs in which well-defined synchronized communities appear and interact with one another [3].…”
Section: Introductionmentioning
confidence: 99%
“…Investigators studying the latter have found that many complex networks have a modular structure involving motifs [1], communities [2,3], layers [4], or clusters [5]. For example, recent work has shown that as many kinds of networks (including isotropic homogeneous networks and a class of scale-free networks) transition to full synchronization, they pass through epochs in which well-defined synchronized communities appear and interact with one another [3]. Knowledge of this structure, and the dynamical behavior it supports, informs our understanding of biological [6], social [7], and technological networks [8].…”
Section: Introductionmentioning
confidence: 99%
“…We define an indicator function h as 2) so that the switch in the system occurs when h(z) = 0. We shall refer to the line v = a as the switching manifold, call F L (F R ) the left (right) half-system of (2.1) and call the region of the plane where…”
Section: Piece-wise Linear Modelsmentioning
confidence: 99%
“…This is expected since the associated network eigenvectors have components that sum to zero, describing perturbations that act to push the oscillations apart pairwise. To quantify this, we introduce the mean field variables (E(v), E(w)), where 2) and trace the mean field signal for a typical large network simulation in Figure 5. Here, it can be seen that the mean field trajectory does not settle down, and moreover is repelled away from the synchronous solution (also plotted).…”
Section: Where G(a; T) Is Given In (26) Andmentioning
confidence: 99%
See 1 more Smart Citation